Understanding the futsal game moments through the eyes of futsal coaches: a comparison of expert and novice coaches - Rodrigues, M.; Leite, N.; Ribeiro, J. N.; Sampaio, J.; Araujo, D.; Travassos, B. (International Journal of Performance Analysis in Sport, 2024)
Coaches rely on the information detected in the performance environment to regulate the quantity and quality of the decisions made during matches. This study used an expert-novice paradigm to describe coaches` gaze behavior in offensive and defensive game moments of futsal. Twenty coaches (ten expert and ten novices) participated in the study. The experimental conditions contrasted their gaze behavior when watching 71 video clips of the game, both when the team was attacking and when the team was defending. The dependent variables for gaze behaviour were organized in game moments and described using biplots from multiple correspondence analysis. Overall, the results revealed a relationship between the coaches` level of expertise and the visual information searched at each futsal game moment. Expert coaches focused more on the information related to the players without the ball and the space, while novice coaches tended to focus their attention in the ball and in the attacker with the ball. It seemed clear that the process of visual exploration is specific for each game moment and that the level of coaches` expertise shapes the visual information searched.